Mechanical behaviour of concrete added with bamboo fibre - Choong, Wai Kit (2015)
The rapid population growth around the world has caused the housing demands to increase rapidly. More infrastructures and buildings are required in order to facilitate the expanding population. This phenomenon has caused the demands on construction materials such as concrete to increase as well. Concrete has many advantages including low cost, high availability, low maintenance, high compressive strength and durability, concrete's low tensile strength requires it to be reinforced with high tensile strength materials. The addition of natural fibre into fresh concrete can increase the ductility of the concrete matrix. This study aims to investigate the workability, compressive strength, and flexural strength of concrete added with bamboo fibre. The addition of bamboo fibre is divided into three different percentages namely 0.5%, 1.0% and 1.5% based on the volume of the concrete mixture. The slump test was carried out to determine the workability of the concrete, while the compression test and flexural test were performed to determine the compressive strength and flexural strength, respectively. The workability and compressive strength decreased when more bamboo fibre was added into the concrete, yet the flexural strength increased when more bamboo fibre was added. In conclusion, this study presents an experimental investigation on the mechanical behaviour of bamboo fibre reinforced concrete.